ChemInform Abstract: Solvent‐Free, [Et3NH][HSO4] Catalyzed Facile Synthesis of Hydrazone Derivatives. Issue 23 (June 2015) - Parveen, Mehtab; Azaz, Shaista; Malla, Ali Mohammed; Ahmad, Faheem; Pereira da Silva, Pedro Sidonio; Ramos Silva, Manuela
Abstract Title compounds [(II) and (IV)] are simply, efficiently, and in high purity synthesized using an eco‐friendly, sustainable protocol where inexpensive [Et3NH][HSO4] serves as the catalyst.